A multimodal in vitro approach to assess the safety of oral care products using 2D and 3D cellular models - Leano, S. Marceli; De Souza, Wanderson; De Vecchi, Rodrigo; Lopes, Amanda; Deliberador, Tatiana; Granjeiro, Jose M. (Frontiers in Toxicology, 2024)
IntroductionPeriodontitis, affecting approximately 3.9 billion individuals globally, significantly impacts quality of life and has raised interest in its potential systemic effects. Sodium perborate, a common component in oral care products for biofilm control, is widely used, though concerns about its safety persist. This study aimed to evaluate the in vitro toxicity of six commercial oral care products and varying concentrations of sodium perborate, utilizing human gingival fibroblasts (HGF) and keratinocytes (HaCat) as cell models.MethodsExperiments were performed in both 2D monolayer and 3D cultures using MTT and electrical impedance assays, adhering to the manufacturer’s recommended exposure time of 30–60 s for product testing. For the reconstructed epidermis model, a prolonged exposure time of 42 min was applied, following the Organization for Economic Cooperation and Development (OECD) Test Guideline 439.ResultsResults indicated that all products and sodium perborate at 1 mg/mL were cytotoxic in monolayer cultures. However, at concentrations relevant to commercial formulations (0.06 mg/mL sodium perborate), no significant toxicity was observed. In contrast, the 3D culture models, including spheroids and reconstructed epidermis, exhibited minimal to no cytotoxic effects for the commercial products, with sodium perborate showing no significant toxicity below 0.1 mg/mL. The reconstructed epidermis model, used as surrogate for oral mucosa, further confirmed that the products were non-irritating, in compliance with OECD TG 439 standards.DiscussionThis study highlights the importance of considering exposure time, dosage, and cellular model when assessing the safety of oral care products. While 2D models are useful for preliminary screenings, 3D models provide a more physiologically relevant assessment, emphasizing the need for robust testing protocols to ensure product safety.